2022
DOI: 10.1093/hmg/ddac132
|View full text |Cite
|
Sign up to set email alerts
|

Novel genes and sex differences in COVID-19 severity

Abstract: Here we describe the results of a genome-wide study conducted in 11 939 COVID-19 positive cases with an extensive clinical information that were recruited from 34 hospitals across Spain (SCOURGE consortium). In sex-disaggregated genome-wide association studies for COVID-19 hospitalization, genome-wide significance (p < 5x10−8) was crossed for variants in 3p21.31 and 21q22.11 loci only among males (p = 1.3x10−22 and p = 8.1x10−12, respectively), and for variants in 9q21.32 near TLE1 only among females (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 68 publications
3
46
0
1
Order By: Relevance
“…We revealed that rs17763742 and rs13071258 are in complete LD ( R 2 = 1; D’ = 1) in European population; the other two SNPs are in weak LD to rs13071258 in European population, with R 2 = 0.08 for rs13071258 vs. rs115679256 and R 2 = 0.43 for rs13071258 vs. rs17763742. We confirmed that most of these published COVID-19 SNPs by Cruz et al ( Cruz et al, 2022 ) are replicable in the current sex-stratified COVID-19 GWASs in either males or females. The lack of replication of sex-biased differential associations for these SNPs in current study may attribute to the relatively small sample sizes of current UK Biobank GWASs.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…We revealed that rs17763742 and rs13071258 are in complete LD ( R 2 = 1; D’ = 1) in European population; the other two SNPs are in weak LD to rs13071258 in European population, with R 2 = 0.08 for rs13071258 vs. rs115679256 and R 2 = 0.43 for rs13071258 vs. rs17763742. We confirmed that most of these published COVID-19 SNPs by Cruz et al ( Cruz et al, 2022 ) are replicable in the current sex-stratified COVID-19 GWASs in either males or females. The lack of replication of sex-biased differential associations for these SNPs in current study may attribute to the relatively small sample sizes of current UK Biobank GWASs.…”
Section: Resultssupporting
confidence: 88%
“…We further evaluated previously published COVID-19 risk SNPs showing genome-wide significant association signals in either females/males or both sexes published by Cruz et al (Cruz et al, 2022) in the currently used UK Biobank COVID-19 hospitalization GWASs. We obtained summary statistics of nine genome-wide significant SNPs emerged in sex-unstratified or sex-stratified COVID-19 GWASs from Cruz and colleagues ( Cruz et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations